Planejamento tributário e a norma geral antielisiva - Fernandes, Bruna Oliveira (2014)
The tax obligation is compulsory and arises out of law, thus, on the taxable fact being carried out, the taxpayer cannot refuse to pay the charge or tax. Aiming to reduce the tax burden, many taxpayers have programmed their actions on a lawful basis in order to opt for the alternative conducts to the event of tax incidence, avoiding the occurrence of the taxable fact. This practice has been called tax avoidance or tax planning. Tax avoidance is not to be mistaken by tax evasion, which is an unlawful conduct to avoid the payment of the tax due. To avoid planning, which reduces tax revenue, the tax authorities and part of the doctrine or legal writings defend the possibility of disregarding the acts and alternative business so that one can characterize them as taxable facts because they have levied pronouncement of economic capacity. This attempt by the tax authorities, which gave rise to the sole paragraph of article 116 of CTN (the anti-tax planning general rule), intends to render any practice of tax planning fruitless by enhancing the German theory of economic interpretation of tax laws. Said legal provision authorizes disregarding legal acts and business that unbind the hypothesis of tax incidence, allowing taxation by the economic aspects of the transaction made by the taxpayer, and even though they are different businesses, the effects are the same, and taxation shall be performed. The use of economic interpretation for taxation of cases of tax planning is the introduction, in disguise, of the likewise method in tax law and the relaxation of the principle of tributary legality. Brazilian Constitution, on setting forth the legal security and the tributary legality, prohibited the use of analogy to the exigency of tribute, which only resulted from the law. Evidence wealthy condition to be taxed is not sufficient; there must be the legal provision on a cumulative basis. Tax authorities do not have the competence to equate distinct legal transactions to tax them equally, albeit under the pretext of promoting of fiscal justice. Fighting tax planning should be done by the legislative branch and through specific manner, and where capacity to pay is found, the lawmaker is authorized to introduce taxes. The right to effectiveness of tax planning is based on freedom, free enterprise and private autonomy and it is safeguarded by the principle of tributary legality